Homo Ludens, Aksi-Drama, Film Ek HOMO LUDENS & PINK PASTEL; AKSI DRAMA DALAM FILM EKSPERIMENTAL DENGAN PENDEKATAN ABJECT ART - Eka Wahyu Primadani, Eka Wahyu Primadani; Fossy Biosa, Sito; Waret Khunacharoensap (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
Abstract art has penetrated the world of film. Taboo things and disgusting actions are present forcing the spectators to enjoy them with this statement of art movement. This phenomenon emerged and art writers studied it, until they succeeded in drawing a common thread about the relationship between Homo Ludens (playing humans), drama and film with artistic research (based on artistic practice); example: drama and action-acting always have cases that are never finished being discussed in film works, especially in the experimental film movement. Things that arise from the "ego" of the artist (director) become material to be dissected from a broad perspective, good and bad, positive and negative, acceptance to rejection, involving discussions related to disturbing effects that cannot be separated from elements of rejection of the works. "Elegant and neat", especially when discussing art or artistic works of an abstract or subjective nature, shows something that challenges the limits of normality, which is another normality that should be accepted by "new audiences". Describes a structure or system that can refer to something that specifically questions aesthetics, physicality, looks rude, bad gestures are taboo to be not taboo, satirizes institutions, degrades, demeans, protests, or is sarcastic towards people who live normal lives. The identity of his work is formed through a process of resistance that produces clearly delineated action-reaction deviations between different circumstances. This shows how we can interpret "bad" aesthetics, full of suffering from the experiences of the people around us, presented in action drama works with characteristics such as something disgusting, strange or strange, closeness to something with a satirical nuance, is an important component of a critical statement by the director of the film PINK PASTEL to activate awareness of opposing perceptions from an optimistic attitude about changes in drama narrative styles, to further exploring in films from increasingly intelligent spectators, ambitions against conventional or normal action-drama at the level of normality. general reality